1986
DOI: 10.1111/j.1600-0897.1986.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental Lesions in Maternal Autoimmune Diseases

Abstract: We have investigated the presence and clinical implications of maternal vascular lesions and chronic villitis of unknown etiology (CVUE) in 18 placentas of 15 mothers with several autoimmune diseases (AD), including, for the first time, idiopathic thrombocytopenic purpura, autoimmune thyroid diseases, and multiple sclerosis. The group with AD had significantly more maternal vascular lesions and CVUE than the control group. We did not find lesions that could be attributed to any of the diseases in particular. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 32 publications
1
29
0
3
Order By: Relevance
“…The available data on the relationship between complement activation and growth retardation appear to be conflicting: some studies have reported that complement levels were significantly lower in mothers of SGA infants than in controls [34], suggesting that the immunological derangement leads to placental lesions and growth restriction. On the contrary, others indicate that complement activation is associated with IUGR and other pathologic pregnancy outcomes (such as preeclampsia and recurrent spontaneous abortions) [35]. In particular, it has been reported that C5 [36], as well as C3a activation [37], are crucial intermediary events (in the first trimester of pregnancy) in the pathogenesis of IUGR.…”
Section: Immune Mechanisms and Iugrmentioning
confidence: 98%
“…The available data on the relationship between complement activation and growth retardation appear to be conflicting: some studies have reported that complement levels were significantly lower in mothers of SGA infants than in controls [34], suggesting that the immunological derangement leads to placental lesions and growth restriction. On the contrary, others indicate that complement activation is associated with IUGR and other pathologic pregnancy outcomes (such as preeclampsia and recurrent spontaneous abortions) [35]. In particular, it has been reported that C5 [36], as well as C3a activation [37], are crucial intermediary events (in the first trimester of pregnancy) in the pathogenesis of IUGR.…”
Section: Immune Mechanisms and Iugrmentioning
confidence: 98%
“…In both of these diseases, these lesions were related to poor fetal outcome. Placental vascular damage with deposits of IgM, C3, and C1q was more prominent in a patient with SSc and these lesions were related to poor fetal outcome [25]. Thus, we are convinced that systematic placental examination might help to identify the role of placental vasculopathy in pregnancy outcome [23].…”
Section: Placentamentioning
confidence: 99%
“…Con probabilidad, la placenta fue de pequeñ o tamañ o, inferior al percentil 10 o incluso al percentil 5 del peso placentario teó rico para la edad de gestació n, con cambios sugestivos de vasculopatía decidual, con o sin signos de aterosis aguda, aumento de nudos nucleares sincitiotrofoblá sticos, con vellosidades hipermaduras (hipoplasia vellosa distal), signos todos ellos asociados a insuficiencia uteroplacentaria cró nica, altamente sugestivos de preeclampsia 42 . Sin embargo, se han descrito hallazgos superponibles en pacientes con LES, esclerosis sisté mica, SAF y otras enfermedades autoinmunes sin preeclampsia 43 . Por tanto, tampoco los datos histopató logicos placentarios podrían haber sido definitivos.…”
Section: Imitadores De La Preeclampsiaunclassified